Bound-to-continuum and two-phonon resonance, quantum-cascade lasers for high duty cycle, high-temperature operation - Faist, Jérôme; Hofstetter, Daniel; Beck, Mattias; Aellen, Thierry; Rochat, Michel; Blaser, Stéphane (My University, 2002)
Recent advances in quantum-cascade (QC) laser active-region design are reviewed. Based on a rate equation model of the active region, we show why new gain regions. based on a two-phonon resonance or a bound-to-continuum transition exhibit significantly better performance than the traditional design based on a three-quantum-well active region. Threshold current densities as low as 3 kA/cm2 at T = 300 K, operation with a peak power of 90 mW at 425 K, single-mode high-power operation up to temperatures above 330 K at λ ≈ 16 μm and continuous wave operation up to T = 311 K are demonstrated. QC lasers able to operate at high duty cycles (50%) on a Peltier cooler were used in a demonstration of a 300-MHz free-space optical link between two buildings separated by 350 m.
Keywords: intersubband; laser; mid-infrared